2009
DOI: 10.1007/s00431-009-1020-2
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal treatment in two Dutch families with pyridoxine-dependent seizures

Abstract: Incidental reports suggest that antenatal treatment of pyridoxine dependent seizures (PDS) may improve neurodevelopmental outcome of affected patients. Two families with PDS are reported, both with two affected siblings. Antenatal treatment with pyridoxine was instituted during the second pregnancy in each family (50 and 60 mg daily from 3 and 10 weeks of gestation, respectively). Perinatal characteristics and neurodevelopmental outcome at 4 (Family A) and 12 (Family B) years of age were compared between the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…Analysis of the outcome of patients homozygous for the same common severe mutation E399Q can reflect this impact. Some patients with this mutation can have substantial developmental delay and seizures that are not completely controlled with pyridoxine (group 3; e.g., Bennett et al 2009, patient K3020), whereas two other patients homozygous for this same mutation but treated prenatally with a high dose of pyridoxine had a normal developmental outcome (Bok et al 2010) (group 1). Yet, prenatal treatment with pyridoxine alone does not completely protect against developmental delay (Rankin et al 2007) reflecting additional complexity beyond prenatal treatment alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the outcome of patients homozygous for the same common severe mutation E399Q can reflect this impact. Some patients with this mutation can have substantial developmental delay and seizures that are not completely controlled with pyridoxine (group 3; e.g., Bennett et al 2009, patient K3020), whereas two other patients homozygous for this same mutation but treated prenatally with a high dose of pyridoxine had a normal developmental outcome (Bok et al 2010) (group 1). Yet, prenatal treatment with pyridoxine alone does not completely protect against developmental delay (Rankin et al 2007) reflecting additional complexity beyond prenatal treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility could be a deficiency limited to a region or a specific cell type in the brain. Direct toxicity of α-amino adipic semialdehyde binding to proteins or abnormalities in GABA metabolism have been proposed (Bok et al 2010; Gospe 2002). The activity of α-aminoadipic semialdehyde dehydrogenase on other substrates such as betaine aldehyde and trans -2-nonenal opens the possibility of other contributing toxic substances (Brocker et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…suggested that antenatal pyridoxine supplementation may be effective in preventing intrauterine seizures, decreasing the risk of complicated birth and improving neurodevelopmental outcome in PDE. [16]…”
Section: Discussionmentioning
confidence: 99%
“…More recently, another disorder of amino acid synthesis was treated prenatally with apparent success in two families affected by pyridoxine-dependent seizures (Bok et al ., 2010). Maternal oral treatment with pyridoxine was given during the second pregnancy in each family and outcomes were compared with the first untreated pregnancy.…”
Section: Therapy For Fetal Inborn Errors Of Metabolismmentioning
confidence: 99%